1989
DOI: 10.1007/bf00004123
|View full text |Cite
|
Sign up to set email alerts
|

Sulfur cycling in a forested Sphagnum bog in northern Minnesota

Abstract: Abstract.The mass balance and internal cycle of sulfur within a small forested, Sphagnum bog in northern Minnesota are presented here based on a 4-year record of hydrologic inputs and outputs (precipitation, throughfall, streamflow, upland runoff) and a 3-year measurement of plant growth and sulfur uptake. Concentrations and accumulation rates of inorganic and organic sulfur species were measured in porewater. The bog is a large sink for sulfur, retaining 37% of the total sulfur input. Because of the relativel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
76
0
1

Year Published

1994
1994
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(84 citation statements)
references
References 88 publications
(108 reference statements)
7
76
0
1
Order By: Relevance
“…The reduced S species may be pyrite, organic S and H 2 S. It is likely that pyrite was the dominant reduced compound as Fe/Cl was also three times lower in August than in March. Many studies have shown that accumulation of Fe-sulphides is of minor importance in peatlands (Brown, 1985;Wieder, 1988;Urban et al, 1989). However, although inorganic species such as pyrite are not important pools of S, they may be important as intermediate short term products which transform to organic S (Brown, 1985(Brown, , 1986Urban et al, 1989).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The reduced S species may be pyrite, organic S and H 2 S. It is likely that pyrite was the dominant reduced compound as Fe/Cl was also three times lower in August than in March. Many studies have shown that accumulation of Fe-sulphides is of minor importance in peatlands (Brown, 1985;Wieder, 1988;Urban et al, 1989). However, although inorganic species such as pyrite are not important pools of S, they may be important as intermediate short term products which transform to organic S (Brown, 1985(Brown, , 1986Urban et al, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…S0 4 may be too unreactive for a direct chemical incorporation into organic matter. High pH, high Fe concentrations and high S0 4 concentrations have been proposed to enhance the formation of pyrite (Urban et al, 1989), conditions which are fulfilled at H2 and H4. The accumulated amorphous Fe-sulphides, if present, should be extracted by both pyrophosphate and oxalate extractant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bayley et al 1986;Urban et al 1989;Spratt and Morgan 1990). Sulfur retention apparently is not the result of a fraction of the incoming S atoms becoming immobilized within the peat, with the remaining fraction passing through the peatland unaltered.…”
mentioning
confidence: 99%
“…Rather, the biogeochemical cycling of S in peat is quite dynamic. The quantity of S that cycles internally through oxidation and reduction reactions in peat may far exceed S inputs (Urban et al 1989;Spratt and Morgan 1990;Wieder et al 1990). Subsurface peaks in total S, organic S, and FeS,-S concentrations, typically I Corresponding author.…”
mentioning
confidence: 99%